Democracy delayed : the case of Castro's Cuba - López, Juan J. (Juan José) (Johns Hopkins University Press, 2002)
"More than a decade after the fall of the Berlin Wall, Castro remains in power, with no sign that the Cuban government or economy is moving toward liberalization. In Democracy Delayed, political scientist Juan J. Lopez offers a searching and detailed analysis of the factors behind Cuba's failure to liberalize."